Perancangan Sistem E-Booking Eyelash Lirace Studio Berbasis Website - Hanifa Azzahra; Hamdan Hamdan; Sunardi Sunardi (BETRIK, 2025)
The rapid development of information technology has encouraged digital transformation across various sectors, including the beauty service industry. Lirace Studio, a provider of eyelash extension services, still faces challenges in managing reservations, which are currently handled manually through instant messaging. This approach often leads to recording errors, overlapping schedules, and limited payment methods. This study aims to design and develop a web-based e-booking system to improve service efficiency at Lirace Studio. The research method applied is Rapid Application Development (RAD), consisting of requirement planning, prototype design, system construction, and cutover (implementation and testing). The system was developed using the Laravel framework with a MySQL database and a responsive user interface. Testing was carried out using Black Box Testing to evaluate system functionality and User Acceptance Testing (UAT) to assess user acceptance levels. The results show that all core features, such as registration, login, service booking, rescheduling, online payment, and admin data management, functioned as expected. UAT involving 15 respondents indicated an average acceptance rate of 88.87%, which categorizes the system as highly feasible.